2018
DOI: 10.1136/bmjopen-2018-023935
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the socioeconomic patterning of overweight/obesity in India: a repeated cross-sectional study using nationally representative data

Abstract: ObjectivesWe aimed to examine trends in prevalence of overweight/obesity among adults in India by socioeconomic position (SEP) between 1998 and 2016.DesignRepeated cross-sectional study using nationally representative data from India collected in 1998/1999, 2005/2006 and 2015/2016. Multilevel regressions were used to assess trends in prevalence of overweight/obesity by SEP.Setting26, 29 and 36 Indian states or union territories, in 1998/99, 2005/2006 and 2015/2016, respectively.Participants628 795 ever-married… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 38 publications
15
54
2
Order By: Relevance
“…Setting these limitations aside, the study by Corsi and Subramanian 4 demonstrates broad-scale impact of chronic disease across the entirety of the socioeconomic spectrum. Alongside their findings, the best available published data indicate that chronic diseases are rapidly rising in India: the prevalence of overweight and obesity has more than doubled between 1998 and 2016 among women with no education, 8…”
Section: + Related Articlementioning
confidence: 94%
“…Setting these limitations aside, the study by Corsi and Subramanian 4 demonstrates broad-scale impact of chronic disease across the entirety of the socioeconomic spectrum. Alongside their findings, the best available published data indicate that chronic diseases are rapidly rising in India: the prevalence of overweight and obesity has more than doubled between 1998 and 2016 among women with no education, 8…”
Section: + Related Articlementioning
confidence: 94%
“…Overall, the majority of the participants were either overweight or obese. A recent nationwide study done by Luhar S et al 15 in rural areas in India found around 15%-32% increases in overweight/obesity prevalence among all individuals from 1998-2016, irrespective of Socioeconomic patterning. Sengupta A et al 16 in a study among women in various states across India documented that overweight problem has started expanding from urban and well-off women to the poor and rural people, while the rural-urban and rich-poor difference has disappeared.…”
Section: Cardio-metabolic Risk Profilementioning
confidence: 96%
“…The grouping of BMI data into the different categories of malnutrition is based on the WHO de nitions. These cut off point has been used to allow the comparison with other studies [20][21][22][23].…”
Section: Study Outcomesmentioning
confidence: 99%